IDENTIFIKASI JENIS TUMBUHAN OBAT TRADISIONAL DI KAWASAN HUTAN OLAT CABE DESA BATU BANGKA KECAMATAN MOYO HILIR KABUPATEN SUMBAWA BESAR - Husnul Jannah; Safnowandi Safnowandi (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2018)
The purpose of this study was to identify the types of traditional medicinal plants in the Olat Cabe Forest Area of Batu Bangka Village, Moyo Hilir Subdistrict, Sumbawa Besar District. This type of research is explorative descriptive research. Descriptive research in this study was to reveal information about the types of traditional medicinal plants in the Olat Cabe Forest Area of Batu Bangka Village, Moyo Hilir Subdistrict, Sumbawa Besar District using the snowball sampling method. The approach used is a qualitative approach. The population in this study were all types of traditional medicinal plants found in the Olat Cabe Forest Area of Batu Bangka Village, Moyo Hilir Subdistrict, Sumbawa Besar District. While the samples in this study were traditional medicinal plants in the Olat Cabe Forest Area of Batu Bangka Village, Moyo Hilir Subdistrict, Sumbawa Besar District. Data collection techniques used are observation and interview. Data analysis techniques use univariate statistics such as mean, median, mode, standard deviation, and variance. The purpose of descriptive analysis is to find out the description or distribution of sample or population data. Descriptive analysis was chosen based on the measurement scale. For nominal and interval data, descriptive analysis techniques that can be done are only modes, while interval and ratio scale data can be done by all descriptive analysis techniques. The results of the study identified 40 types of medicinal plants, from 25 families and 40 genus types of medicinal plants commonly used by the community.